2016
DOI: 10.1016/j.psyneuen.2016.01.024
|View full text |Cite
|
Sign up to set email alerts
|

PTSD is associated with an increase in aged T cell phenotypes in adults living in Detroit

Abstract: Background Psychosocial stress is thought to play a key role in the acceleration of immunological aging. This study investigated the relationship between lifetime and past-year history of post-traumatic stress disorder (PTSD) and the distribution of T cell phenotypes thought to be characteristic of immunological aging. Methods Data were from 85 individuals who participated in the community-based Detroit Neighborhood Health Study. Immune markers assessed included the CD4:CD8 ratio, the ratio of late-different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 45 publications
4
36
0
Order By: Relevance
“…Because T-reg cells are critical for containing pro-inflammatory responses and Th1 and Th17 cells activate inflammatory responses (Afzali et al, 2007), these alterations in the composition of T-cell subsets may act in aggregate to direct systemic inflammatory tone into an overdrive state in PTSD (Jergovic et al, 2014). Finally, immunological aging of T-cell phenotypes has also been associated with PTSD (Aiello et al, 2016).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%
“…Because T-reg cells are critical for containing pro-inflammatory responses and Th1 and Th17 cells activate inflammatory responses (Afzali et al, 2007), these alterations in the composition of T-cell subsets may act in aggregate to direct systemic inflammatory tone into an overdrive state in PTSD (Jergovic et al, 2014). Finally, immunological aging of T-cell phenotypes has also been associated with PTSD (Aiello et al, 2016).…”
Section: Ptsd and Inflammationmentioning
confidence: 99%
“…Aiello et al [70•] showed that PTSD was associated with lower CD4/CD8 T-cell ratios and a greater number of late-stage (relative to naïve) T-cells. These results were obtained in a sample of 85 adults with extensive community trauma histories and analyses controlled for chronological age, suggesting that PTSD might be accelerating this age-related immune process.…”
Section: Traumatic Stress and Inflammation And Immune Responsementioning
confidence: 99%
“…Notably, systemic inflammation may underlie the pathophysiology of PTSD, as well as the consistent link between PTSD and chronic medical conditions associated with aging, such as cardiovascular, metabolic, autoimmune, and neurodegenerative diseases [4][5][6][7][8], and other markers of accelerated aging [6,7,[9][10][11][12][13][14]. This dysregulated inflammatory state is itself partially coordinated by maladaptive alterations of hypothalamic-pituitary adrenal (HPA) axis activity and sympathetic nervous system (SNS) sensitivity/responsivity [15,16], which affect both peripheral immune cells in blood and neuroimmune dynamics in brain.…”
Section: Introductionmentioning
confidence: 99%